Language as a means of creating an «external» image of the country (based on the language of Moscow Russia of the XVI century) (Eurasian Journal of Philology Science and Education, 2018)
The article is devoted to the language situation in Muscovy, which was characterized in the XVIcentury by complexity and contradictions. The author of the article has conducted the analysis of languagein connection with history of the state, its culture and peculiarities of intercultural communicationof people as native speakers in the transitional period of Russia’s development. As a result of the studyof the Slavic and Western European scientists opinions, views of foreign observers, the material of theearly ABCs and grammars , the conclusion is drawn that throughout the XVI century the language ofMuscovy did not possess the internal unity and monolithicity (consolidation), which was reflected in theexistence of several hypostases of the Russian language, being in the relationship of complementarity,interconnection and sometimes of combination. It is proved that for a century such fuzzy, illogical relationsof different forms of language had a significant influence on the formation of the potential image ofthe actual Russian language and the Russian people in the outside world. It is argued that understandingof the linguistic and extra-linguistic factors of speech situation inside the country, taking into accountthe view from the side can give a sufficiently adequate and objective overview of the relevant people.